A perfluorobutylpentane (F4H5)‐based solution for the removal of residual emulsified silicone oil. Issue 1 (14th June 2017) - Chan, Yau Kei; Cheng, Ho Ching; Wu, Jing; Tang, Yuk Heng Matthew; Chan, San To; Wong, David; Shum, Ho Cheung
Abstract: Purpose: The emulsification of silicone oil (SO) is associated with many complications. In this study, we investigate a new SO solvent, perfluorobutylpentane (F4H5) with 1% by volume of perfluorinated polyethers–polyethylene glycol–perfluorinated polyethers (PFPE‐PEG‐PFPE) triblock copolymer, for removing emulsified droplets. Methods: An in vitro 3D printed model eye chamber was used to evaluate the efficiency of the three test liquids in removing SO droplets, namely saline, F4H5 and F4H5 with surfactant PFPE‐PEG‐PFPE. The numbers of SO droplets were quantified using a Coulter Counter. The stability of double emulsion formed was tested with a fluidic device based on electro‐coalescence. Two retinal cell lines were used to test the biocompatibility of the liquids. Results: The mean number of droplets remaining in the eye chamber after rinsing with a solution of F4H5 with surfactant was 13 315 ± 4620/ml compared to saline (23 460 ± 7595/ml; p   <   0.05). The double emulsion was found to be highly stable. The biocompatibility of F4H5 and the surfactant was similar to that of the saline control. Conclusion: By adding a small amount of surfactant, the resultant F4H5 solution is able to promote double emulsification and remove more SO droplets. Although further in vivo safety studies are necessary before clinical trials, the result of our study suggests that F4H5 with surfactant is a promising Rinsing Solution for removing emulsified droplets. This work therefore translates a well‐known phenomenon in emulsion science to tackle the emulsification problem observed in the routine vitreoretinal surgery.